Metal powder for laminate molding mixed with oxide nanoparticle and laminate molded body
By incorporating oxide nanoparticles with a limited area ratio into Ni or Fe alloy powders for additive manufacturing, the challenges of achieving high temperature strength and flowability are addressed, resulting in enhanced mechanical properties and improved manufacturing efficiency.
Patent Information
- Application Number
- JP2024232730
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2024-12-27
- Publication Date
- 2025-04-10
- Estimated Expiration
- 2041-12-01
AI Technical Summary
Existing metal powders for additive manufacturing face challenges in achieving high temperature strength and suitable flowability due to issues with particle agglomeration and dispersion of oxide nanoparticles.
The use of Ni or Fe alloy powder materials with oxide nanoparticles that have not been surface-treated with organic matter, where the nanoparticles are deposited at a ratio of 10% or less in area ratio, to enhance high temperature strength and flowability through improved particle dispersion.
This approach results in a metal additive manufacturing body with excellent high temperature strength and improved flowability, as the finely dispersed oxide nanoparticles enhance the mechanical properties and reduce adhesion between metal particles.
Smart Images

Figure 2025060973000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to a metal powder for additive manufacturing mixed with particles made of an oxide having a size on the nanometer order (hereinafter referred to as oxide nanoparticles), and to an additive manufactured body additively manufactured using this powder. [Background technology]
[0002] A method for manufacturing three-dimensional objects by irradiating a powder material with a laser or electron beam (hereafter referred to as "additive laser sintering") is known. A light beam is irradiated onto a powder layer made of metal powder to form a sintered layer, and a method for manufacturing metal powder for metal laser sintering, which is used in metal laser sintering to obtain a three-dimensional object by stacking the sintered layers, has been proposed. Representative methods for metal laser sintering include the powder bed method (powder bed fusion method) and the metal deposition method (directed energy deposition method).
[0003] In the powder bed method, the irradiated areas of the spread powder are melted and solidified by irradiation with a laser beam or electron beam. This melting and solidification bonds the powder particles together. Irradiation is selectively performed on a portion of the metal powder, and the non-irradiated areas do not melt, and a bond layer is formed only in the irradiated areas.
[0004] New metal powder is laid on top of the bonded layer and irradiated with a laser or electron beam. The metal particles melt and solidify due to the irradiation, forming a new bonded layer. The new bonded layer also bonds with the existing bonded layer.
[0005] The melting and solidification caused by irradiation is repeated in sequence, causing the assembly of bonding layers to gradually grow. This growth results in a three-dimensional object. Using this type of additive manufacturing method, objects with complex shapes can be easily produced.
[0006] As an additive manufacturing method using a metal deposition method (directed energy deposition method), for example, a manufacturing method has been proposed for a powder for metal laser sintering in which a light beam is irradiated onto a powder layer made of metal powder to form a sintered layer and obtain a three-dimensional shaped object, in which an "iron-based powder" and "one or more types of powder selected from the group consisting of nickel, nickel-based alloys, copper, copper-based alloys, and graphite" are mixed together (see Patent Document 1).
[0007] In this type of metal additive manufacturing, powder flowability is important in order to spread the powder with high packing properties. The most well-known method for improving powder flowability is to increase the circularity of the powder.
[0008] In addition, a method has been proposed in which oxide nanoparticles that have not been surface-treated with organic substances are mixed with metal particles of an Fe-based alloy to improve fluidity, thereby reducing the adhesive force between the metal powder particles (see Patent Document 2). However, because the oxide nanoparticles used are not surface-treated with organic substances, the nanoparticles tend to aggregate more easily than surface-treated nanoparticles, and therefore a classification process using a jet mill is required to obtain a powder material that does not contain areas where the nanoparticles have aggregated (called nanoparticle aggregates).
[0009] Incidentally, regarding high-temperature strength, a method is known that is not additive manufacturing, but involves mixing metal raw materials with oxide nanoparticles, and then solidifying the mechanically alloyed powder material by HIP to form a material with fine oxides dispersed in the metal structure and exhibiting excellent high-temperature strength (see Non-Patent Document 1). Mechanically alloyed powders with dispersed oxides include MA6000 and MA754 for Ni-based alloys, and MA956 for Fe-based alloys. However, mechanically alloyed powders have low sphericity and are not necessarily suitable for fluidity and packing. [Prior art documents] [Patent documents]
[0010] [Patent Document 1] JP 2008-81840 A [Patent Document 2] Patent Publication No. 2021-75784 [Non-Patent Document 1] Yoshiya Kaieda, "Development Trends of Ceramic Dispersion Strengthened (ODS) Heat-Resistant Alloys", Turbo Machinery, Vol. 13 (1985) No. 4 Summary of the Invention [Problem to be solved by the invention]
[0011] In order to produce an additive manufacturing body with excellent high-temperature strength by additive manufacturing using metal powder, it is preferable to use a metal powder with a high packing density, but it is difficult to obtain the desired sphericity by ordinary mechanical alloying. In addition, in mechanical alloying, the particles are repeatedly rolled and folded, and pressed together and crushed to form an alloy, so oxides are not necessarily dispersed on the surface.
[0012] Therefore, the problem to be solved by the present invention is to provide a powder for metal additive manufacturing that has excellent high-temperature strength, and an additive manufactured object that has excellent high-temperature strength produced using this powder for additive manufacturing. [Means for solving the problem]
[0013] Therefore, after extensive research, the inventors have discovered that a Ni-based or Fe-based alloy powder material for metal additive manufacturing in which oxide nanoparticles that have not been surface-treated with an organic substance are attached to the surface of the alloy powder particles at an area ratio of 10% or less, with the aim of particle dispersion strengthening (ODS), and that using this powder material to manufacture objects by metal additive manufacturing, has excellent high-temperature strength.
[0014] The means for solving the problems of the present invention is an alloy powder material for additive manufacturing consisting of a Ni-based alloy powder or an Fe-based alloy powder having oxide nanoparticles attached to the powder surface that has not been surface-treated with an organic substance.
[0015] The oxide nanoparticles are preferably such that the area ratio of the oxide nanoparticle agglomerates adhering to the surface of the alloy powder material is 10% or less, more preferably 5% or less, and from the viewpoint of particle dispersion strengthening (ODS), preferably 0.1% or more.
[0016] The amount of the oxide nanoparticles added is preferably 0.1 to 1.5 mass % or less.
[0017] The primary particle diameter of the oxide nanoparticles is preferably within the range of 1 to 100 nm.
[0018] The oxide nanoparticles are Y 2 O 3 , ThO 2 , Al 2 O 3 , TiO 2 , SiO 2 Preferably, Y is any one of the following: 2 O 3 , Al 2 O 3 and more preferably Y 2 O 3 It is.
[0019] The metal additive manufacturing body is produced by additive manufacturing using these alloy powder materials for additive manufacturing. Effect of the Invention
[0020] When additive manufacturing is performed using the alloy powder for additive manufacturing according to the present invention, oxides are finely dispersed in the shaped body, resulting in a shaped body that exhibits excellent high-temperature strength.
[0021] When the amount of oxide nanoparticles added increases, oxide nanoparticle agglomerates tend to occur on the surface of the mixed powder. Although the nanoparticle agglomerates diffuse in the melt pool during laser melting and are dispersed throughout, if the area ratio of the nanoparticle agglomerates becomes excessively large, some of the nanoparticle agglomerates do not disperse completely and remain as μm-scale agglomerated oxides. Such residual μm-scale oxides occur when the area ratio of the nanoparticle agglomerates exceeds 10% or more.
[0022] If the area ratio of the oxide nanoparticle agglomerates on the surface of the alloy powder for additive manufacturing is kept within 10% as in the present invention, when the powder is melted in additive manufacturing, the agglomerates of the oxide nanoparticles melt and disperse as fine oxides of tens to hundreds of nm, so that the additive manufacturing body is strengthened by particle dispersion strengthening. On the other hand, if it exceeds 10%, the agglomerates of the nanoparticles are not sufficiently dissolved during melting, and μm-scale oxide nanoparticle agglomerates tend to remain, and these μm-scale oxides tend to become the starting points of fracture, which tends to reduce the strength.
[0023] By adhering oxide nanoparticles to the metal powder surface, the oxide nanoparticles are positioned between the metal powder particles, resulting in the metal powder particles no longer coming into direct contact with each other and reducing the adhesive force acting between these particles, thereby improving the fluidity of the alloy powder material. [Brief description of the drawings]
[0024] [Figure 1] 1 shows scanning electron microscope (SEM) images of nickel-based alloy powder material with oxide nanoparticles of the present invention attached to the surface, where (a) shows the case where 0.01 mass% of Y2O3 is added, and (b) shows the case where 0.3 mass% of Y2O3 is added. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0025] [Preparation of atomized powder as the base material for the test material] As base powders for the examples and comparative examples of the present invention, powder materials with the component compositions shown in Table 1 below were produced by gas atomization. Gas atomization was carried out by melting raw materials mixed in a predetermined ratio in an alumina crucible in a vacuum using high-frequency induction heating, dropping the molten alloy from a nozzle with a diameter of about 5 mm below the crucible, and spraying it with high-pressure argon or high-pressure nitrogen. The average particle diameter D of the obtained powder was 50 (μm) and sphericity. The average particle size here is the volume average.
[0026] Specifically, the Ni-based alloy equivalent to Inconel 718 is: (No.A)Fe-52%Ni-20%Cr-0.05C-0.1Mn-0.2Si-3.0Mo-0.3Co-5.2Nb-0.5Al-0.9Ti-0.003B, (No.B)Fe-52%Ni-20%Cr-0.05C-0.1Mn-0.2Si-3.0Mo-0.3Co-5.2Nb-0.5Al-0.9Ti-0.003B, In addition, as an Fe-based alloy equivalent to SUS630, (No. C) Atomized powder with the composition Fe-16Cr-4Ni-4Cu-0.9Mn-0.4Nb-0.25Si-0.05C was prepared.
[0027] [Table 1]
[0028] [Mixing metal powder and oxide nanoparticles] As oxide nanoparticles, CIK Nanotech Co., Ltd.'s Y 2 O 3 Nanoparticles (average particle size 29 nm) were used. To prepare alloy powders with oxide nanoparticles attached to the surface, mechanical mixing was performed using a V-type mixer. Powders can also be mixed using a tumbler mixer, ball mixer, or other tools to the extent that they are intended to be attached to the surface of the metal powder. They can also be mixed manually in a container.
[0029] [Removal of unattached oxide nanoparticles] Even after these mixing steps, oxide nanoparticles that are not attached to the metal powder particles may remain. The oxide nanoparticles are several μm to several hundred μm in size. Therefore, these unattached oxide nanoparticles were removed by sieving. By going through this removal process, a more suitable mixed powder material can be obtained.
[0030] [Production of tensile and rupture test specimens using metal additive manufacturing] Using the powder with nanoparticles attached to its surface after the above treatment, tensile test pieces and rupture test pieces were prepared by the following two methods. (i) Test pieces were produced by metal additive manufacturing using a mixed powder of No. A Ni-based alloy (31.2 μm) in Table 1 and No. C Fe-based alloy (31.2 μm) in Table 1 using the selective laser sintering (SLM) method. (ii) Test specimens were fabricated by metal additive manufacturing using the binder jet method using mixed powder of Ni-based alloy (8.3 μm) No. B in Table 1. It is needless to say that the additive manufacturing method using the powder of the present invention is not limited to these techniques, and additive manufacturing can also be performed using electron beam powder sintering additive manufacturing (EBM) or laser deposition methods. However, in this example, we will use test pieces produced by the two methods described above for evaluation.
[0031] [Metal powder morphology] Alloy powder size: 2μm≦D 50 ≦150μm If the size of the alloy powder is less than 2 μm, the powder flowability is significantly reduced due to excessive pulverization, while if it exceeds 150 μm, the powder packing rate is reduced and the density of the molded body is reduced. Therefore, the size of the alloy powder is set to 2 μm≦D 50 ≦150μm.
[0032] The suitable particle size range varies depending on the additive manufacturing method, as follows: By adjusting the size of the alloy powder according to these methods, it is possible to obtain an appropriate layered object. Selective Laser Sintering (SLM): 10≦D 50 ≦45μm Laser deposition method, electron beam method: 45≦D 50 ≦150μm Binder jet method: 2≦D 50 ≦25μm
[0033] [Oxide nanoparticle morphology] Size of oxide nanoparticles: preferably 1 to 100 nm in primary particle diameter The oxide nanoparticles preferably have a primary particle diameter of 1 to 100 nm. Since the smaller the particle diameter, the greater the effect of particle dispersion strengthening (ODS) during additive manufacturing, the size of the oxide nanoparticles is more preferably 1 to 50 nm, and even more preferably 1 to 30 nm. The primary particle diameter of the mixed powder to which the oxide nanoparticles are attached is the same as the primary particle diameter of the oxide nanoparticles before mixing, and the primary particle diameter can be determined based on specific surface area measurement by gas adsorption method.
[0034] Nanoparticle addition amount: 0.1-1.5% The amount of nanoparticles added to the alloy powder of the present invention can be 0.1 to 1.5% by mass. If it is less than 0.1%, the effect of particle dispersion strengthening (ODS) cannot be obtained sufficiently. If it is 1.5% or more, oxide agglomerates are likely to occur, and the strength decreases. The amount of nanoparticles added is preferably 0.2 to 1.5%, and more preferably 0.25 to 1.0%.
[0035] Nanoparticle shape and manufacturing method: Examples of methods for producing oxide nanoparticles that have not been surface-treated with organic substances include the flame spray pyrolysis method (FSP method). In order to prevent excessive aggregation of oxide nanoparticles, it is effective to use oxide nanoparticles with high sphericality, so oxide nanoparticle powders obtained by the physical vapor synthesis method have higher sphericality than those obtained by the FSP method, making it easier to obtain desirable powders.
[0036] Types of oxide nanoparticles: The oxide nanoparticles of the present invention include, for example, Y 2 O 3 , ThO 2 , Al 2 O 3 , TiO 2 , SiO 2 The oxide nanoparticles are not limited to these exemplified oxides, and are suitable as long as they can exist stably in the matrix even at high temperatures. 2 O 3 , Al 2 O 3 is preferred because it can exist stably in the matrix even at high temperatures. 2 O 3 It is. In the examples, Y is used as a representative oxide nanoparticle. 2 O 3 It is explained using.
[0037] [Area ratio of oxide nanoparticles agglomerated part] In the present invention, the area ratio of agglomerated portions of oxide nanoparticles attached to the surface of the alloy powder is 10% or less. If the area ratio of nanoparticle agglomerates is 10% or less, when the powder is melted during additive manufacturing, the agglomerates of nanoparticle oxides melt and disperse as fine oxides measuring tens to hundreds of μm, and the additive manufacturing object is strengthened by ODS. On the other hand, if the content is 10% or more, the nanoparticles do not disaggregate sufficiently during melting, and μm-scale oxides remain. These μm-scale oxides can become the starting point of fracture, reducing the strength of the molded object.
[0038] If the purpose is to improve fluidity, the amount of nanoparticles added is sufficient if it is between 0.01% and 0.1%, but in order to achieve particle dispersion strengthening (ODS), it is necessary to add 0.1% or more oxide nanoparticles. If the amount of nanoparticles added is increased to 0.1% or more, agglomerations of 1 μm or more will inevitably occur.
[0039] [Heat treatment of the model] The test pieces after molding were subjected to the following heat treatment. (Ni-based alloy) Solution treatment: After holding at 980°C for 1 hour, the material was air-cooled. Aging treatment: After holding at 720°C for 8 hours, the material was furnace cooled (in 2 hours) to 620°C, held at 620°C for 8 hours, and then air cooled. (Fe-based alloy) Solution treatment: After holding at 1040°C for 1 hour, the material was water-cooled. Aging treatment: After holding at 480°C for 2 hours, the specimen was air-cooled.
[0040] [Evaluation of the area ratio of nanoparticle agglomerates] Thirty particles of the alloy powder material with oxide nanoparticles attached are observed using a scanning electron microscope (SEM). Next, energy dispersive X-ray analysis (EDS) is used to identify whether it is a metal or an oxide. The portion where the particle diameter calculated from the area exceeds 1 μm is defined as an oxide nanoparticle agglomeration portion, and the area ratio of the nanoparticle agglomeration portion is calculated by the following formula. Area ratio of oxide nanoparticle agglomerates = (total area of oxide nanoparticle agglomerates observed in one alloy powder particle) / (area of one powder particle) Here, (the area of one powder particle) only counts the part visible in the SEM image (the overlapping parts that are not visible are not counted). This calculation is carried out for 30 powder particles, and the average value is taken as the area ratio of the oxide nanoparticle agglomerates.
[0041] [D 50 Measurement method] Average particle diameter D 50 In the measurement, the total volume of the powder is taken as 100% and a cumulative curve is obtained. The particle diameter at the point on this curve where the cumulative volume is 50% is D 50 Particle diameter D 50 is measured by the laser diffraction scattering method. A suitable device for this measurement is the Microtrac MT3000 laser diffraction / scattering particle size distribution analyzer from Nikkiso Co., Ltd. Powder is poured into the cell of this device together with pure water, and the particle size is detected based on the light scattering information of the particles.
[0042] [Hausner ratio] The Hausner ratio is an index defined as tap density / apparent density. The lower the Hausner ratio, the better the flowability of the powder. The tap density is calculated by measuring the tap density of approximately 50 g of powder in a volume of 100 cm 3 The mixture was packed into a cylinder and evaluated for packing density after dropping from a height of 10 mm and tapping 200 times.
[0043] [High temperature tensile strength] Using alloy powder material, type 6 test pieces (φ6 × GL30 mm) described in Table A-3 of the Japanese Industrial Standard JIS G0567 (2020) were produced by additive manufacturing (SLM or binder jet method). Using these test pieces, the maximum tensile stress σ applied during the tensile test was calculated as the tensile strength (σ = measurement load F / cross-sectional area S). The tensile test was carried out in an environment of 649°C.
[0044] [Rupture Test] Creep rupture test specimens with a parallel portion having a diameter of 6 mm were prepared under the following conditions. Rupture tests (fracture tests) were conducted under the following conditions. ·Ni-based alloy: 649℃, 690MPa ·Fe-based alloy: 482℃, 665MPa
[0045] As shown in Tables 2 and 3, the amount of oxide nanoparticles added to Ni-based alloys No. A and No. B, and Fe-based alloy No. C in Table 1 was changed, and mixed powder materials, Example Nos. 1 to 5, Reference Examples Nos. 6 to 7, and Comparative Examples Nos. 1 to 7, were produced. These were then subjected to additive manufacturing, and the properties of each were evaluated by the above-mentioned method. The results are shown in Tables 2 and 3. The combinations of which powders from Table 1 were used are shown in D of Table 2. 50 As shown in FIG. 1, Ni-based alloy No. B in Table 1 is used in Example No. 2 in Table 2 and Comparative Example No. 2 in Table 3. The oxide nanoparticles used in the examples and comparative examples were all Y 2 O 3 It is.
[0046] [Table 2]
[0047] [Table 3]
[0048] As shown in FIG. 1, 0.3% by mass of Y 2 O 3 It was confirmed that nanoparticle agglomerations were generated in the samples to which nanoparticles were added.
[0049] The additively shaped bodies made of the Ni-based alloy powder of the Examples all had higher tensile strength and were less likely to break than the additively shaped bodies made of the Ni-based alloy powder of the Comparative Examples, and exhibited excellent high-temperature strength. The additively shaped bodies made of the Ni-based alloy powder of the Examples all had higher tensile strength and were less likely to break than the additively shaped bodies made of the Ni-based alloy powder of the Comparative Examples, and exhibited excellent high-temperature strength. The additively shaped bodies made of the Fe-based alloy powder of the Reference Examples all had higher tensile strength and were less likely to break than the additively shaped bodies made of the Fe-based alloy powder of the Comparative Examples, and exhibited excellent high-temperature strength.
[0050] Furthermore, the Hausner ratio was low in the examples, indicating excellent fluidity, and it was confirmed that the alloy powder is suitable as an alloy powder material for additive manufacturing.
[0051] Comparative Ni-based alloy No. 2 and comparative Fe-based alloy No. 6 both had poor fluidity and did not flow, so that the apparent density could not be measured and the Hausner ratio could not be evaluated. In this way, although these alloys were not suitable as alloy powder materials for additive manufacturing in the past, by adding oxide nanoparticles as in the present invention, they became suitable for additive manufacturing and had excellent high-temperature strength. [Industrial Applicability]
[0052] The alloy powder material of the present invention is suitable for metal powder for additive manufacturing using metal deposition method, powder bed method, electron beam method, and binder jet method. The additive manufactured body is also suitable for heat-resistant parts.
Claims
1. Powder surface is not treated with organic matter. 2 O 3 The Ni-based alloy powder having oxide nanoparticles adhered thereto is an alloy powder material to which 0.1 to 1.50 mass% of oxide nanoparticles are added, and the area ratio of the oxide nanoparticle agglomerates adhering to the surface of the alloy powder material is 0.1% to 10%.
2. The alloy powder material for additive manufacturing according to claim 1, characterized in that the oxide nanoparticles have a primary particle diameter in the range of 1 to 100 nm.
3. 3. The alloy powder material for additive manufacturing according to claim 1 or 2, characterized in that the alloy powder material is oxide nanoparticles produced by physical vapor synthesis.
4. A metal additive manufacturing product produced by additive manufacturing using the alloy powder material for additive manufacturing according to any one of claims 1 to 3.
5. Ni-based alloy powder that has not been surface-treated with organic substances produced by physical vapor phase synthesis. 2 O 3 The method for producing an alloy powder material for additive manufacturing includes adding 0.1 to 1.50 mass% of oxide nanoparticles of the above-mentioned oxide nanoparticles and mixing them to adhere the oxide nanoparticles to the Ni-based alloy powder, and then removing the unadhered oxide nanoparticles by classification, thereby producing an alloy powder material for additive manufacturing in which the area ratio of oxide nanoparticle agglomerates adhering to the surface of the alloy powder material is 0.1% to 10%.
Citation Information
Patent Citations
Metal-based nano composite powder material, preparation method and application thereof
CN111230098A
Method for treating powder and powder treated by said method
JP2016041850A
Methods of manufacturing dispersion-strengthened materials
JP2021134428A
Additively manufactured oxide dispersion strengthened medium entropy alloys for high temperature applications
US20200399744A1
Powder material
WO2021090918A1